Kajian Prosedur Pemindahan Arsip: Studi Kasus Di Bank Indonesia - Fitri Susiani (Diplomatika: Jurnal Kearsipan Terapan, 2019)
This paper describes the procedure for transferring records carried out by Bank Indonesia. Transfer of records is one part of the shrinking program archive. Transfer of records is important to do to protect records that have a use value and to avoid stacking records. The data used in the study are primary data and secondary data. Primary data were obtained from observations or participatory observations, in-depth interviews with records managers, as well as studies of archival policies issued by Bank Indonesia. The secondary data in the form of an assessment of library materials. The conclusion obtained from this paper is the transfer of records at Bank Indonesia using two methods, namely conventional methods and application-based methods. Guidelines for moving records have also been referring to international standards, namely ISO 15489-2016. The facilities and infrastructure used in the transfer of records are also in accordance with archival standards with adequate capacity. In carrying out the activities of the shrinking of the archive was not found significant obstacles.